2019
DOI: 10.1002/14651858.cd001532.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for primary vesicoureteric reflux

Abstract: Analysis 2.2. Comparison 2 Surgical reimplantation of ureters plus antibiotics versus antibiotics alone, Outcome 2 Renal parenchymal defects (scars and thinning) on IVP: unit of analysis (children).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 110 publications
3
41
0
4
Order By: Relevance
“…For this reason, NNT is subject to interpretation of the attending physician as to whether CAP might be considered moderately or even slightly beneficial. In addition, when deciding on management strategy, the rising concerns about uropathogen and multi-drug resistance to CAP needs to be balanced with the expected benefit of preventing new renal scarring [12,14,16,17,25,45,55]. In contrast, not only the prevention of renal scarring needs to be taken into account but also the often severe symptoms associated with fUTI, especially in small children [35].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, NNT is subject to interpretation of the attending physician as to whether CAP might be considered moderately or even slightly beneficial. In addition, when deciding on management strategy, the rising concerns about uropathogen and multi-drug resistance to CAP needs to be balanced with the expected benefit of preventing new renal scarring [12,14,16,17,25,45,55]. In contrast, not only the prevention of renal scarring needs to be taken into account but also the often severe symptoms associated with fUTI, especially in small children [35].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the data showing possible benefits of antibiotic treatment, it is important to consider that VUR often persists for years, meaning that antibiotic prophylaxis is often needed for a prolonged duration. In contradiction to the studies above, a 2019 Cochrane review reported that long-term antibiotic prophylaxis “makes little or no difference to the risk of repeat UTI causing a person to be unwell” ( 34 ). Other studies also suggest that prophylactic antibiotic therapy can often be discontinued without incurring significantly increased UTI rates ( 75 ).…”
Section: Treatment Approachesmentioning
confidence: 96%
“…Also, the most recent Cochrane review on interventions for primary VUR (47) showed that antibiotic prophylaxis had insignificant difference to the risk of new/ continuous renal damage in patients followed with DMSA scans.…”
Section: Does Surgical Intervention Change the Future Of These Children?mentioning
confidence: 99%